CHALLENGES IN TRANSMITTING STUDENT-RESEARCHER RECOMMENDATIONS: THE CASE OF MASTER'THESES ON CLIMATE CHANGE - Idah RAZAFINDRAKOTO (Universitaria Publishing House, Craiova, 2021)
The contribution of scientific research is recognized in the design of development policies. Research thus constitutes a "tank" of capitalized knowledge, such as reflections, knowledge and recommendations for development. Thus, by focusing on the contemporary issue of climate change on the environment of Madagascar, this article examines the recommendations made by the student researchers in their Master' theses. However, the observation of the exclusion and disregard of student researchers is reported. Then, this article diagnoses the reasons for communicational cuts and blockages in the process of transmitting their recommendations for the construction of policies. This study therefore deciphers the challenges that hinder the transmission of recommendations between student researchers at the University of Antananarivo and their state recipients.